Exploiting dual-dielectric devices to produce photonic hooks - Riley J. A. Joseph Arnold; Minin O. V. Oleg Vladilenovich; Minin I. V. Igor Vladilenovich; Pacheco-Pena V. Victor (2022, 2022)
Title screen